The engineering design process - Ertas, Atila; Jones, Jesse C. (Chichester, 1996)
"Combines all relevant techniques used in the thermal and materials sciences, fluid engineering, and engineering mechanics to foster an understanding of the engineering design process from the recognition of a need and the definition of design objectives, through product certification and manufacture of a prototype. Coverage includes insight on how to manage a project, safety and environmental protection, plus a unique chapter concerning ethics. This edition has been updated to incorporate current trends and environmental and economic issues. Mini projects stress such topics as codes and specifications, economical design, statistical data analysis, simulation and modeling, creativity, and innovation. Features actual case studies."